Low Risk of Japanese Encephalitis in Short‐Term Australian Travelers to Asia. Issue 3 (8th March 2013) - Ratnam, Irani; Leder, Karin; Black, Jim; Biggs, Beverley‐Ann; Matchett, Elizabeth; Padiglione, Alex; Woolley, Ian; Panagiotidis, Theo; Gherardin, Tony; Luxemburger, Christine; Torresi, Joseph
Abstract : The risk of Japanese encephalitis (JE) in travelers is unknown. In this prospective study, we investigated the incidence of JE in 387 short‐term Australian travelers visiting Asia over a 32‐month period from August 2007 to February 2010 by performing pre‐ and post‐travel antibody testing. No travelers were infected with JE virus during travel, indicating a low risk of infection for short‐term travelers.